1984
DOI: 10.1037/0022-006x.52.6.997
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a revised Jesness Inventory I-Level Classification with delinquents.

Abstract: The use of interpersonal maturity level (I-level) classification has been limited by the unavailabilty of an objective, convenient, and quick method for arriving at the classification. This study examined the validity of a hand-scorable, mechanical procedure for deriving I-level subtypes with a sample of serious delinquents. The system uses T scores on nine empirically developed subtype scales based on item analysis of responses to the Jesness Inventory. The sample comprised 1,131 delinquents tested in 1966-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…In contrast to the findings in pathologically disinhibited subjects, Kagan and colleagues (Kagan, Reznick, & Snidman, 1987, 1988 found that children characterized by behavioral inhibition and shyness demonstrated higher heart rate than their (nonpathological) less in- 458 E,MEZZACAPPA et al hibited counterparts. Garralda, Connell, and Taylor (1991), found that children with emotional disturbances demonstrated hyper-responsiveness of heart rate to aversive consequences during mental tasks, when compared with conduct-disordered children and nonclinical controls.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast to the findings in pathologically disinhibited subjects, Kagan and colleagues (Kagan, Reznick, & Snidman, 1987, 1988 found that children characterized by behavioral inhibition and shyness demonstrated higher heart rate than their (nonpathological) less in- 458 E,MEZZACAPPA et al hibited counterparts. Garralda, Connell, and Taylor (1991), found that children with emotional disturbances demonstrated hyper-responsiveness of heart rate to aversive consequences during mental tasks, when compared with conduct-disordered children and nonclinical controls.…”
Section: Introductionmentioning
confidence: 90%
“…. 1986Jesness & Wedge. 1984Martin, 1981), Data from mother and teacher reports on the Social Behavior Questionnaire were available at 6,9.…”
Section: Assessment Of Anxiety and Antisoeial Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the Jesness Inventory, employed in this dissertation, was designed to tap "… the generalized disposition to resolve problems of social and personal adjustment in ways ordinarily regarded as showing a disregard for social customs or rules" (Jesness, 1969: 45). Further, the Jesness Inventory has been found to be successful in predicting offending among juveniles as well as adults (Caldwell, Silvermand & Lefforge, 2004;Jesness, 1986;Jesness & Roberts, 1983;Pinsoneault, 1999;Posey, 1988) and to be associated with recidivism (Jesness 1983;Jesness & Wedge, 1984). The Anti-Social Attitudes subscale of the Jesness Inventory contains 30 true/false items (e.g., "When you're in trouble, it's best to keep quiet about it") and six of the 30 items displayed substandard item-to-total correlations (these six items are italicized in Table 2).…”
Section: Role-takingmentioning
confidence: 99%
“…In the application of I-levels a personality test was developed by Jesness (1966) as an alternative to A detailed investigation was made of judgements on each criterion used in arriving at the characteristics as weighted scale scores which are in common, but also individual characteristics including idiosyncratic characteristics of the normative sample. It was found, for example, that the level of agreement using weighted scale scores from the prediction programme (overall 11.9 per cent, with 3 I per cent by I-level and 25.3 per cent by I-type) was not as satisfactory as the unweighted scores on three Jesness subscales which were found to discriminate significantly between treatment groups (overall 31.0 per cent, comprising social anxiety scale 69 per cent by I-type, and value orientation scale 66.7 per cent and immaturity scale 64.3 per cent by I-level).…”
mentioning
confidence: 99%